As concepções de ensino-aprendizagem de uma professora de inglês: uma relação entre prescrição e ação - Viana, Juliana Pontes (2010)
This research aimed at investigating how a State School English teacher understands the material prescribed by the São Paulo State Educational Department and implements it in the classroom. This is a study whose support are the concepts of prescribed and implemented work by Amigues (2004) and Souza-e-Silva (2004) among others; the official documents published by the Federal and State educational departments to guide the teachers practices (São Paulo, 2008; Brasil, 1998); the main teaching-learning theories and language studies which focus on Vygotsky s studies (1934/2000;1987/1998;2001); the reflective practices (Freire, 1996; Giroux, 1997; Smyth, 1992). The research methodology used was the critical collaborative research (Magalhães, 2007), and data was collected by means of video recordings of classes and audio recordings of reflective sessions. For data analysis and interpretation, the categories employed were those of prescribed and implemented work (Souza-e-Silva, 2004) for classroom actions, as well as the quality of interactions (Marcuschi, 2008) and reflective actions (Smyth, 1992; Liberali, 2004; 2008). Results obtained after analysis reveal that the teacher-participant renormalizes the prescriptions by developing them with the support of her professional experience. The research also reveals that despite the attempts by the teacher-researcher to introduce a challenge to the incoherence presented in the work, so as to allow for changes in the teacher-participant s practices to take place, the former s questions were not as strong as they ought to have been to provoke the latter s reflections